2015
DOI: 10.1038/onc.2015.94
|View full text |Cite
|
Sign up to set email alerts
|

XactMice: humanizing mouse bone marrow enables microenvironment reconstitution in a patient-derived xenograft model of head and neck cancer

Abstract: The limitations of cancer cell lines have led to the development of direct patient derived xenograft (PDX) models. However, the interplay between the implanted human cancer cells and recruited mouse stromal and immune cells alters the tumor microenvironment and limits the value of these models. To overcome these constraints, we have developed a technique to expand human hematopoietic stem and progenitor cells (HSPCs) and use them to reconstitute the radiation-depleted bone marrow of a NOD/SCID/IL2rg−/− (NSG) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 46 publications
(49 reference statements)
0
110
0
3
Order By: Relevance
“…40 The implantation of tumor cells in these mice permitted to highlight a specific immuno-response stimulated by the growth of the tumor. 42,43 Very recently, Morton et al 43 reported that by adding purified Tat-MYC and Tat-Bcl2 fusion proteins to cultured HSPCs the number of CD34+ cells markedly expanded, while transduced HSPCs retained the ability to differentiate into either myeloid or lymphoid cells, thus recapitulating both lineages of the human immune system. Interestingly, i n head and neck PDXs, the relationship between the tumor and immune system was similar to the one found in the patient in whom the tumor originated was observed.…”
Section: Mouse Species Advantages Limitationsmentioning
confidence: 99%
“…40 The implantation of tumor cells in these mice permitted to highlight a specific immuno-response stimulated by the growth of the tumor. 42,43 Very recently, Morton et al 43 reported that by adding purified Tat-MYC and Tat-Bcl2 fusion proteins to cultured HSPCs the number of CD34+ cells markedly expanded, while transduced HSPCs retained the ability to differentiate into either myeloid or lymphoid cells, thus recapitulating both lineages of the human immune system. Interestingly, i n head and neck PDXs, the relationship between the tumor and immune system was similar to the one found in the patient in whom the tumor originated was observed.…”
Section: Mouse Species Advantages Limitationsmentioning
confidence: 99%
“…Recently, lethally irradiated NOD SCID gamma mice humanized with cord blood hematopoietic stem cells (known as XactMice) were developed (Morton et al 2015). This model enables study of HNSCC in a microenvironment educated by human cytokines, T and B cells, and stroma.…”
Section: Tumor Immune Network and Relationship With Cancer Stem Cellsmentioning
confidence: 99%
“…In this case, some murine growth factors and cytokines do not interact with their human counterpart receptors, orthotopic tumors vascularize more significantly than do subcutaneous tumors, and implantation to inguinal rather than thoracic fat pads show improved engraftment rates [44]. Humanization of tumor microenvironment to support tumor engraftment and growth [45] and its manipulation to narrow tumor-microenvironment gap [46] that recently produced Xactmice [47] are two interesting areas that add to the improved modeling of human tumors in mice.…”
Section: Generation Of Xenograft Modelsmentioning
confidence: 99%